Feasibility of Material, Language and Media Aspects in the Development of Statistics Textbooks for Physical Education at IKIP Budi Utomo Malang - Wardathi, Amy Nilam; Pradipta, Anangga Widya (Universitas Nusantara PGRI Kediri, 2019)
Textbooks are supporting the success of learning. A varied and complete textbook will support learning so that it is easier to reach the goal. One of the compulsory subjects in the Physical Health and Recreation Education (PJKR) study program in Statistics. Based on the results of observations of researchers, a statistical book for sports education has never been developed, whereas based on needs analysis, a statistical textbook for sports education needs to be developed. Therefore, this study aims to develop a statistical textbook whose material content is related to sports using the 4D development model. Consisting of the stages of defining, designing, developing, and disseminating. This paper specifically describes in detail at the developing stage, which describes the feasibility of the material, language and media aspects of the book from the validator. Based on the results of the validation from material experts, languages and the media, it shows that textbooks are suitable for use in the field